2021
DOI: 10.33963/kp.15990
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiovascular disease, cardiovascular drug therapy, and in-hospital outcomes in patients with COVID-19: data from a large single-center registry in Poland

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…The results of data processing in a cohort observational design study using a metaanalysis showed that the use of antiplatelet drugs effectively reduced mortality in COVID-19 patients. Similar results were found in a study conducted in England by Abu-Jamous et al (2020) and Benson et al (2021); Israel by Merzon et al (2021); Poland by Terlecki et al (2021); China by Yuan et al (2020); America by Osborne et al (2021) and Sahai et al (2021).…”
Section: Discussionsupporting
confidence: 83%
“…The results of data processing in a cohort observational design study using a metaanalysis showed that the use of antiplatelet drugs effectively reduced mortality in COVID-19 patients. Similar results were found in a study conducted in England by Abu-Jamous et al (2020) and Benson et al (2021); Israel by Merzon et al (2021); Poland by Terlecki et al (2021); China by Yuan et al (2020); America by Osborne et al (2021) and Sahai et al (2021).…”
Section: Discussionsupporting
confidence: 83%
“…Also, lower exercise capacity before infection, assessed by the New York Heart Association (NYHA) classification, adversely influenced the outcome. The association between heart failure and adverse outcomes in COVID-19 patients was reported for the general population previously [3,4].…”
Section: Resultsmentioning
confidence: 86%
“…We really appreciated the results of the observational study conducted by Terlecki et al [1], who demonstrated that, in a total of 1729 patients admitted to hospital due to coronavirus disease 2019 (COVID-19), history of diabetes mellitus significantly increased the odds of in-hospital death by 53%, while those patients with concomitant heart failure (HF) experienced a two-fold increase in the corresponding odds. Researchers have also shown in their cohort that prior treatment with renin-angiotensin-aldosterone system blockers, statins, antiplatelet drugs, or beta-blockers was associated with a significant decrease in the odds of in-hospital death, confirming a protective role of these drug classes against the most surrogate COVID-19 outcome [1].…”
Section: To the Editormentioning
confidence: 98%
“…Therefore, it would be very interesting and would increase a value of the initial report, if Terlecki et al [1] could provide data concerning the usage rates of SGLT-2 inhibitors in their cohort and the association with crude outcomes, such as mechanical ventilation and in-hospital death, since this "miraculous" drug class has attracted scientific interest, with an established role in the secondary prevention of cardiovascular disease. Data from such real-world studies may influence decision-making and improve therapeutic strategy if we confront another COVID-19 pandemic wave in the near future.…”
Section: To the Editormentioning
confidence: 99%